How Canada can help global adolescent health mature - Ashley Vandermorris; Zulfiqar A Bhutta (BMC, 2017)
Abstract Background There is an emerging focus on adolescent health within the global health community as we come to recognize that the adolescent years are formative in determining health and health-related behaviours across the life-course. Such attention is not only relevant on the global scale but is imperative in Canada as well. Main body This commentary provides a brief review of recent investments targeting global adolescent health and presents five potential avenues for action which emerged out of the recent Canadian Partnership for Women and Children's Health (CanWaCH) Global Adolescent Health conference. These avenues are: (1) Demand data; (2) Embrace complexity; (3) Be holistic; (4) Engage adolescents; and (5) Commit to Canada. Conclusion As international agencies signal their commitment to global adolescent health, Canada is well-positioned to lead this call to action by espousing the fundamental adolescent health tenets of advocacy, equity, justice, and collaboration in order to move this critical agenda forward.